Health and safety in early years and childcare : contextualising health and safety legislation within the Early Years Foundation Stage - Laverty, Bernadina; Reay, Catherine (National Children's Bureau, 2014)
A practical guide to health and safety in early years settings with a step-by-step guide to the law, compliance and practical application.